Identifying the challenges faced by working single mothers in Kuala Lumpur: the reasons for their non-participation in assistance programmes - Abdul Rahman, Shukran; Zambri, Madzwin Ansari (International Academy of Sciences, Engineering, and Technology, 2017)
This paper reports the findings of a research, which studies the challenges faced by working single mothers; and the reasons for their non-participation in financial assistance programmes. Four working single mothers ranged in age from 40 to 67 were interviewed to gather in-depth information on the challenges and reasons. Their challenges include financial and time constraints; lack of knowledge and skills; social stigma; lack of childcare facilities and strict working hours. Despite the availability of assistance programmes, they did not participate, because of their negative experiences; and negative perceptions towards assistance-providing agencies. Interventions are recommended for relevant authorities and agencies to boost the images of the assistance-providing agencies; to increase the awareness and level of trust of the public on the assistance programmes providers.